2008
DOI: 10.1177/003335490812300413
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic Disparities in Stroke Recognition in Individuals with Prior Stroke

Abstract: SYNOPSISObjective. Studies of stroke awareness suggest that knowledge of early warning signs of stroke is low in high-risk groups. However, little is known about stroke knowledge among individuals with a history of prior stroke who are at significant risk for recurrent stroke.Methods. Data from 2,970 adults with a history of prior stroke from the 2003 Behavioral Risk Factor Surveillance System were examined. Recognition of the five warning signs of stroke and appropriate action to call 911 was compared across … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 25 publications
(54 reference statements)
1
19
0
Order By: Relevance
“…10 The reasons for the high proportion of participants who identified cocaine use as a stroke risk factor are not clear, but may be related to high rates of use in this and surrounding communities and the high proportion of individuals who live below the poverty line. 11 Our results are in keeping with other analyses of the BRFSS data where Hispanics had lower overall stroke literacy, 6-8,12 though we did not collect data on household income or educational achievement to correct for these important covariates. The differences noted between Hispanics and African Americans are interesting given the similar burden of risk factors and stroke incidence in both groups at younger ages and reflect an important need to understand how to best educate these at-risk patients.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…10 The reasons for the high proportion of participants who identified cocaine use as a stroke risk factor are not clear, but may be related to high rates of use in this and surrounding communities and the high proportion of individuals who live below the poverty line. 11 Our results are in keeping with other analyses of the BRFSS data where Hispanics had lower overall stroke literacy, 6-8,12 though we did not collect data on household income or educational achievement to correct for these important covariates. The differences noted between Hispanics and African Americans are interesting given the similar burden of risk factors and stroke incidence in both groups at younger ages and reflect an important need to understand how to best educate these at-risk patients.…”
Section: Discussionsupporting
confidence: 81%
“…5 Analyses from the BRFSS in men and women from 2003 to 2005 have identified Hispanic ethnicity, being uninsured, earning less than $35,000 per year, and not completing high school as associated with poor stroke and heart disease literacy. [6][7][8] In our study we aimed to explore stroke literacy in Central Harlem, a predominantly African American (two-thirds of all residents) urban population with a high proportion of the population living under the federal poverty level (New York City Department of Health, 2000). We further aimed to delineate whether there were any differences based on race/ethnicity or gender.…”
mentioning
confidence: 99%
“…Sixty-five percent of stroke patients seen in an inpatient rehabilitation facility stated they would call 9-1-1 if they thought they were having a stroke [35]. These findings were lower than reported by Ellis and Egede [15 ]in their examination of national data from the US Centers for Disease Control, who found that 83% of stroke survivors knew to call 9-1-1 as a first action in the event of having a stroke. Finally, overall knowledge of stroke was reported in 1 study by Sullivan and Waugh [36] based on data collected from survivors of TIA and stroke using the Stroke Knowledge Test (SKT) [37].…”
Section: Resultsmentioning
confidence: 98%
“…Because stroke survivors are at an increased risk of recurrent stroke, it is critical that they understand stroke symptoms and the need to seek urgent care in the event of experiencing such symptoms. Data suggest that knowledge of stroke symptoms may be low in both the general population and among stroke survivors [13,14,15,16,17]. Poor recognition of stroke symptoms has been attributed to delayed seeking of treatment.…”
Section: Introductionmentioning
confidence: 99%
“…100 Even among those with a history of prior stroke, the ability to recognize stroke symptoms and the need to activate emergency medical services remains poor, with lower performance among non-Hispanic blacks or African Americans (22.3%) and Hispanic/other group members (16.7%) than among whites (28.9%). 101 Hispanic ethnicity remained an independent predictor of lack of awareness in multivariate models. These data indicate that all groups, but particularly minority populations, fall short of the 83% rate of stroke symptom recognition targeted by Healthy People 2010.…”
Section: Differences In Disease Awarenessmentioning
confidence: 93%